Effects of seedlac on soil bacterial diversity: An indication of environmental safety - Kandasamy, Thamilarasi (2025)
Introduction: Lac resin, the only natural resin of animal origin, is exclusively produced by the lac insect (Kerria spp.). It is non-toxic and considered biodegradable. However, the bacteria involved in biodegradation have not been explored. Moreover, the fate of the soil bacteria during biodegradation has not been studied so far. Objective: To explore the fate of soil bacteria due to the burial of seedlac in soil to ascertain whether seedlac is environmentally safe, and to explore the possibilities of identifying any bacterial flora involved in lac biodegradation. Methods: The study began in 2016 by burying seedlac samples (semi-refined lac resin product) in the field soil and pot soil under replicated conditions. The seedlac samples were drawn from the soil in 2019, and the soil adhering to the seedlac samples was used in further experiments. The bacterial diversity of these soils was documented by sequencing the V3-V4 region of 16S rRNA through the Illumina NGS platform. Results: No significant variations were obtained in the soil bacterial diversity between samples except for the marginal increase in the count of Actinobacteria, Myxococcales, Gemmatales, Gemmataceae, the WD2101-soil group in seedlac buried pot soil, and Proteobacteria and Acidobacteria in field soil. Most of these bacterial groups are known to degrade complex organic polymers. Conclusions: Since there are no changes in the soil bacterial diversity due to seedlac burial, it may be concluded that seedlac does not affect the soil microflora and is safe for the soil environment.